2022
DOI: 10.1111/jpc.15907
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a new young adult inflammatory bowel disease transition clinic on patient satisfaction and clinical outcomes

Abstract: Aim The transition from paediatric to adult care for patients with inflammatory bowel disease (IBD) is associated with an increased risk of treatment non‐adherence, hospitalizations and emergency department (ED) use. We established a new young adult IBD clinic (YAC) in Melbourne to capture this at‐risk population. We aimed to assess patient satisfaction as well as clinical outcomes. Methods All patients who attended the YAC between its inception in November 2016 and November 2018 were recruited to our YAC grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Four studies measured patient's comfort in adult care as an outcome of transition (16)(17)(18)(19). Eros et al employed an IBD specific questionnaire (CACHE), which uses a 5-point Likert scale to explore patient's attitudes toward the medical team, accessibility, and facilities of the center (17).…”
Section: Comfort In Adult Carementioning
confidence: 99%
“…Four studies measured patient's comfort in adult care as an outcome of transition (16)(17)(18)(19). Eros et al employed an IBD specific questionnaire (CACHE), which uses a 5-point Likert scale to explore patient's attitudes toward the medical team, accessibility, and facilities of the center (17).…”
Section: Comfort In Adult Carementioning
confidence: 99%
“…Pankaj Garg 1,2 Natasha Reid 1 Teresa Lai 1 Amanda Kent 1 Simone Crewes 1 Kylee Roberts We read with great interest the article by Mollah et al recently published in the Journal of Paediatrics and Child Health that identified how the establishment of a young adult clinic for patients with inflammatory bowel disease (IBD) helped decrease the number of visits to the emergency department (42.9% reduction) and was associated with a favourable outcome in terms of self-reported patients' satisfaction. 1 The authors are to be commended for their effort to emphasise how a transition programme for paediatric patients with IBD may improve relevant outcomes such as avoiding emergency admissions while meeting patients' favour. Indeed, transition programmes are an important tool to increase patients' adherence to care, and eventually improve overall outcomes.…”
Section: Dear Editor Supported Covid-19 Vaccination Pathways For Adol...mentioning
confidence: 99%
“…The COVID-19 pandemic has been a major barrier in the provision of routine ambulatory care services for people with developmental disabilities (DDs). 1 This is even truer for people with challenging behaviours where added complexities preclude access to quality primary health-care services. This is despite the fact that there is emerging evidence that younger people with DDs and comorbidities are at higher risk of COVID-19.…”
Section: Dear Editor Supported Covid-19 Vaccination Pathways For Adol...mentioning
confidence: 99%
“…We feel that our results, and those recently published by Mollah et al further underscore the importance of establishing consistent transition clinics for young patients with IBD as these may help improve the management of this particularly fragile population increasing their adherence to care and decreasing the need for urgent hospitalisations. 1 Giorgia Bodini 1 Francesca Levo 1 Chiara Facchini 1 Silvia Buccilli 1 Serena Arrigo 2 Edoardo G Giannini…”
Section: Dear Editor Transition Programmes For Young Patients With In...mentioning
confidence: 99%
“…We read with great interest the article by Mollah et al recently published in the Journal of Paediatrics and Child Health that identified how the establishment of a young adult clinic for patients with inflammatory bowel disease (IBD) helped decrease the number of visits to the emergency department (42.9% reduction) and was associated with a favourable outcome in terms of self-reported patients' satisfaction. 1 The authors are to be commended for their effort to emphasise how a transition programme for paediatric patients with IBD may improve relevant outcomes such as avoiding emergency admissions while meeting patients' favour. Indeed, transition programmes are an important tool to increase patients' adherence to care, and eventually improve overall outcomes.…”
Section: Dear Editor Transition Programmes For Young Patients With In...mentioning
confidence: 99%